Kebutuhan Pengembangan OPAC Ramah Anak pada Perpustakaan Kementerian Pendidikan dan Kebudayaan - Nadila, Rifa; Rullyana, Gema (Jurnal Ilmu Informasi, Perpustakaan, dan Kearsipan, 2021)
This study aims to determine: (1) priority intention of children’s OPAC development; (2) natural conditions related to children’s OPAC development; (3) discrepancy between expectations and conditions related to children’s OPAC development; (4) priority needs of the most urgent, feasible and appropriate to be implemented in the Library of the Ministry of Education and Culture (Perpusdikbud). Research data resulted over interviews in December 2020 by the librarians of the Perpusdikbud were analyzed using qualitative descriptive approach. The results showed: (1) the development of child-friendly OPAC has not been a priority need; (2) librarians are fully aware concerning to the importance of the development of children's digital literacy, but the level of conditions for service needs and digital collections for children is still low; (3) the discrepancy consists: aspects of leadership decisions, aspects of systems and tools needed in the development of child-friendly OPACs to the human resources of the developers, factors of funds or expenditures required, factors in the quantity of children’s collections, number of users and literacy levels, and adaptation to learning methods to provide user education to the children about the OPAC; (4) the priority needs that are most appropriate to be implemented by the Perpusdikbud at this time is the grading of children's collections. The results of the study concluded that the need for children’s OPAC development in the Perpusdikbud has not been a priority at this time.